Serum fibroscores APRI, FIB-4 and fibroscan in assessment of liver fibrosis in alcoholic associated liver disease - Naik, B. Balakasi; Kumar, Babu; Pughazhendhi, Sultan Nawahirsha (International Journal of Advances in Medicine, 2021)
Background: Alcohol-associated liver disease includes a variety of clinical disorders which include steatosis, Alcoholic steato hepatitis, alcoholic hepatitis of varying degrees of severity, alcoholic cirrhosis, and alcohol associated cirrhosis complicated by hepatocellular carcinoma (HCC). In patients with alcoholic liver disease the presence of hepatic (liver) fibrosis and progression into cirrhosis is a prognostic variable and having impact on survival. To assess hepatic (liver) fibrosis using serum fibro scores fibrosis-4 (FIB-4) scores, AST platelet ratio index (APRI scores) and to compare these results with fibro scan to rule out severe fibrosis in patients with alcohol related disease. Methods: A cross sectional clinical study conducted on 50 patients with alcohol associated chronic liver disease between December 2019 to December 2020 who were in follow up in outpatient department (OPD) and admitted in the Department of Medical Gastroenterology. APRI and FIB-4 scores were calculated and compared with fibro scan values. Results: The results of 50 patients were analysed, including, males with a mean age. Among the study population, 6 (12%) participants had no significant FIB-4, 16 (32%) participants had intermediate FIB-4 and 28 (56%) participants had likely cirrhosis. 33 (66%) participants had no significant APRI, 6 (12%) participants had significant APRI and 11 (22%) participants had cirrhosis liver. Among the people with fibro scan KPA F0-F1 (<7), all of them 100% were no significant FIB-4. Among the people with fibro scan KPA F2 (7 To 9.50), 2 (50%) were no significant FIB-4 and intermediate FIB-4 for each respectively. Conclusions: FIB-4 score correlated better than APRI score in assessing patients with and without severe fibrosis and cirrhosis in the setting of alcohol associated liver disease patients.